Worldmaking after empire - Getachew, Adom. (Princeton)
xii, 271 sayfa
Keywords: “Decolonization revolutionized the international order during the twentieth century. Yet standard histories that present the end of colonialism as an inevitable transition from a world of empires to one of nations—a world in which self-determination was synonymous with nation-building—obscure just how radical this change was. Drawing on the political thought of anticolonial intellectuals and statesmen such as Nnamdi Azikiwe, W.E.B Du Bois, George Padmore, Kwame Nkrumah, Eric Williams, Michael Manley, and Julius Nyerere, this important new account of decolonization reveals the full extent of their unprecedented ambition to remake not only nations but the world. Adom Getachew shows that African, African American, and Caribbean anticolonial nationalists were not solely or even primarily nation-builders. Responding to the experience of racialized sovereign inequality, dramatized by interwar Ethiopia and Liberia, Black Atlantic thinkers and politicians challenged international racial hierarchy and articulated alternative visions of worldmaking. Seeking to create an egalitarian postimperial world, they attempted to transcend legal, political, and economic hierarchies by securing a right to self-determination within the newly founded United Nations, constituting regional federations in Africa and the Caribbean, and creating the New International Economic Order“ --